2015
DOI: 10.1016/j.jvs.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Vascular access in hemodialysis patients older than 80 years

Abstract: Contrary to recent recommendations favoring grafts for hemodialysis in patients older than 80 years, most elderly patients in this study were found to have vasculature that was suitable for autogenous access construction, with patency rates similar to those of their younger counterparts when adequate preoperative planning and postoperative maintenance were carried out. Age alone should not disqualify patients older than 80 years from access surgery for hemodialysis, nor should age disqualify these patients fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 33 publications
3
51
3
2
Order By: Relevance
“…6,13,14 The majority of these reports had selection bias and did not assess the impact of all variables such as anatomy (both vein and artery) and/or clarified their preoperative planning and selection process. In the current study, the age at all three categories (Table 4) failed to reach statistical significance on the outcome of FM and appears to be in favour of recent report published by Olsha et al 15 Furthermore, the authors strongly agree that if a good calibre artery and vein are available, age should not disqualify patients from an autogenous RCAVF that might serve them far better than the aforementioned access types. CHF ¼ congestive heart failure; IHD ¼ ischaemic heart disease.…”
Section: Discussioncontrasting
confidence: 72%
“…6,13,14 The majority of these reports had selection bias and did not assess the impact of all variables such as anatomy (both vein and artery) and/or clarified their preoperative planning and selection process. In the current study, the age at all three categories (Table 4) failed to reach statistical significance on the outcome of FM and appears to be in favour of recent report published by Olsha et al 15 Furthermore, the authors strongly agree that if a good calibre artery and vein are available, age should not disqualify patients from an autogenous RCAVF that might serve them far better than the aforementioned access types. CHF ¼ congestive heart failure; IHD ¼ ischaemic heart disease.…”
Section: Discussioncontrasting
confidence: 72%
“…A summary of the recommendations and suggestions from recently published studies on VA in the elderly are reported in Table 1. Many studies clearly demonstrate a high rate of technical feasibility of fistula construction in the elderly [8, 3133] and age alone should not disqualify patients older than 80 years from access surgery [14, 34]. Nevertheless, it has been shown that in patients aged 67 years or older, only 50.7 % of those with AVF placement initiated dialysis using the AVF, and 43.4 % started with a CVC; in contrast, among patients that received a graft as first access only 25.4 % started dialysis with a CVC; in other words, patients who receive a graft are less likely to require a catheter at first HD treatment compared to those who receive a fistula [15].…”
Section: Va In Elderly Patients: Recent Findingsmentioning
confidence: 99%
“…Data on AVG in the elderly are conflicting. Some studies advocate the use of AVF rather than AVG and provide evidence that in elderly patients autogenous VA may have a patency rate similar to that of younger patients [14]. In contrast, other data support the opposite strategy of ‘AVG first’ in octogenarians and show a higher risk of death before the start of dialysis with AVF than with AVG [15].…”
Section: Introductionmentioning
confidence: 99%
“…But the subsequent patency was similar. Reported patency rates are fairly good in octogenarians [22] , especially if fistulas were created preemptively [19] .…”
Section: Discussionmentioning
confidence: 99%